2022
DOI: 10.1021/acs.analchem.2c01776
|View full text |Cite
|
Sign up to set email alerts
|

QCM-D Investigations of Anisotropic Particle Deposition Kinetics: Evidences of the Hydrodynamic Slip Mechanisms

Abstract: Deposition kinetics of positively charged polymer microparticles, characterized by prolate spheroid shape, at silica and gold sensors was investigated using the quartz microbalance (QCM) technique. Reference measurements were also performed for positively charged polymer particles of spherical shape and the same mass as the spheroids. Primarily, the frequency and bandwidth shifts for various overtones were measured as a function of time. It is shown that the ratio of these signals is close to unity for all ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…Notably, the interfaces create singular contributions such as fluid slippage under particular wetting conditions (e.g., strong hydrophobicity), which tend to reduce the transmission of tangential stress to the resonator and thus the impedance. In fact, QCM has been recently used to unveil slippage in moving fluids, with consequences in biochemical sensors and possibly modifying the relation between Δ f and the coverage (making it linear) of quasi-adsorbed spheres and spheroids . If the particles are strongly hydrophobic, fluid slippage on the particle–fluid interface might also alter the hydrodynamic transmission of momentum to the resonator even if the particle is suspended, an effect which has not been so far studied.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the interfaces create singular contributions such as fluid slippage under particular wetting conditions (e.g., strong hydrophobicity), which tend to reduce the transmission of tangential stress to the resonator and thus the impedance. In fact, QCM has been recently used to unveil slippage in moving fluids, with consequences in biochemical sensors and possibly modifying the relation between Δ f and the coverage (making it linear) of quasi-adsorbed spheres and spheroids . If the particles are strongly hydrophobic, fluid slippage on the particle–fluid interface might also alter the hydrodynamic transmission of momentum to the resonator even if the particle is suspended, an effect which has not been so far studied.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that in NaCl solutions the particle deposition rate was close to the theoretical value predicted from the convective-diffusion approach where the specific surface interactions were neglected. However, one should consider, that the interpretation of the QCM signal in the case of particle load is not unique because it significantly depends on sensor roughness, adhesion strength, and the overtone number. , …”
Section: Introductionmentioning
confidence: 99%
“…However, one should consider, that the interpretation of the QCM signal in the case of particle load is not unique because it significantly depends on sensor roughness, adhesion strength, and the overtone number. 43,48 In ref 11 the deposition of negatively charged spheroidal particles on the PAH-modified mica substrate was determined by AFM.…”
Section: Introductionmentioning
confidence: 99%
“…The repercussion of this slender cognizance of solid–liquid interfacial phenomenon is manifested in the form of overestimation/underestimation of mass which binds on the surface of the sensor. There are several examples of various transducers which are reported to overestimate the amount of analyte detected when correlated with the equations/models that govern their signal response. , Nevertheless, recent works have discovered events such as “liquid slip” previously totally ignored in the response of QCM sensor. , Along similar lines, it remains to be understood if such effects exist in a range of electrochemical and optical sensors that measure binding kinetics in continuous flow conditions of the fluid.…”
mentioning
confidence: 99%